Biological characterisation of a novel and naturally isolated indole alkaloid - Raja, Vijay J. (2015)
Natural products play a pivotal role in the treatment of cancer; identification of compounds such as taxanes and the vinca alkaloids were seminal landmarks in natural product drug discovery. Jerantinine A (JA), a novel Aspidosperma alkaloid isolated from plant species Tabernaemontana corymbosa, was previously reported to possess cytotoxic activity against vincristine-resistant nasopharyngeal carcinoma cells and is therefore an ideal candidate for biological investigation. Furthermore, Tabernaemontana corymbosa has been placed in the endangered list of threatened species by the International Union for Conservation of Nature (IUCN) thus making it a priority to elucidate the biological activity of this alkaloid. Herein, we report detailed biological evaluation of JA on various human-derived carcinoma cell lines. Our preliminary screens showed that significant inhibition of cell growth and colony formation accompanied time- and dose-dependent induction of apoptosis in human cancer cell lines after treatment with JA. Dose-dependent accumulations of cleaved PARP and caspase 3 further confirmed apoptosis. Profound G2/M cell cycle arrest was observed 24 h after treatment in all cell lines. Characteristics of mitotic arrest including inhibition of tubulin polymerisation, microtubule disruption, and aneuploidy were clearly observed. DNA fragmentation was also evident in cells treated with JA. Indeed, significant increases in phosphorylated-γH2AX were indicative of DNA damage caused by double strand breaks and were relatively similar to levels caused by vincristine. Investigations into JA’s ability to overcome vincristine resistance demonstrated that it is not a substrate of Pgp. The role of reactive oxygen species (ROS) in acquired resistance and cell death have also been widely studied. JA induced significant levels of ROS in treated cells, possibly contributing to their apoptotic destiny. Proteomic analyses also corroborated the phenotype of JA-treated cells with increased expression of ROS-neutralising enzymes, aberrant expression of proteins involved in the spindle assembly checkpoint critical to mitosis, and decreased expression in all tubulin proteins detected by LC-MS/MS. A genome-wide RNAi screen revealed several candidate genes involved in mediating sensitivity to JA. The genes corresponding to c-Jun-N-terminal kinases, JNK1/2, were selected for subsequent investigation based on their involvement in multiple pathways that were identified using bioinformatic tools. JNK1/2 were knocked down in MCF-7 and MDA-468 cells and then treated with JA. MTT assays revealed some loss of sensitivity, suggesting that these proteins were indeed involved in mediating cell sensitivity to JA.